The behavioral analysis of dance sports judge's visual searching strategies: Focusing on the skating system - Kim, M.-S.; Lee, K.-K.; Kim, K. (Korean Journal of Sport Biomechanics, 2020)
Objective: The purpose of this study was to investigate the differences between visual search, eye fixation positions, and eye fixation position on whole body regions while judging final matches of dance sports. Method: Ten experienced judges (male 6, female 4) and six dance sports couples belonging to the top Korean leagues in the Korea Dance sports Federation were participated. Wearable eye trackers were used for data collection. The independent t-test was conducted to examine the effects of gender, and the two-way ANOVA was conducted to examine the effects of judges' gender, dance event, and ranking. Results: It was found that the movement of male contestants was preferred, and the gaze fixation was high for torso movements in the judges' evaluations. Moreover, attention was focused on the upper body rather than the lower body; this was maintained for about seven seconds to evaluate each couple. Conclusion: This find was the relative comparison between the two couples was the determining factor in winning or losing.